2020
DOI: 10.1002/cam4.3017
|View full text |Cite
|
Sign up to set email alerts
|

Adherence status to Adjuvant Endocrine Therapy in Chinese Women with Early Breast Cancer and its influencing factors: A cross‐sectional survey

Abstract: Objective: Despite the proven benefits of adjuvant endocrine therapy, adherence to oral endocrine therapy in breast cancer treatment is a substantial problem. The aim of this study was to assess adherence to adjuvant endocrine therapy by women in China for the first 5 years, and to identify its influencing factors. Methods: Stratified sampling method was adopted to select 1875 cases of breast cancer patients for cross-sectional telephone follow-up. Compliance to medications was assessed using the Morisky Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The insufficient and unbalanced medical resources, information disparity between physicians and women with breast cancer, distrust of breast-conserving surgery by some physicians and women, and fear of recurrence are important reasons for the low rate of breast-conserving surgery in China [14]. In addition, for women with breast cancer in China who had received adjuvant endocrine therapy, the nonpersistence rates ranged from 5.9% to 22.6% in years 1-5, and the rate of low compliance ranged from 2.1% to 11.2% [19]. The low compliance with endocrine therapy may be partially explained by inadequate information and social support [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insufficient and unbalanced medical resources, information disparity between physicians and women with breast cancer, distrust of breast-conserving surgery by some physicians and women, and fear of recurrence are important reasons for the low rate of breast-conserving surgery in China [14]. In addition, for women with breast cancer in China who had received adjuvant endocrine therapy, the nonpersistence rates ranged from 5.9% to 22.6% in years 1-5, and the rate of low compliance ranged from 2.1% to 11.2% [19]. The low compliance with endocrine therapy may be partially explained by inadequate information and social support [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for women with breast cancer in China who had received adjuvant endocrine therapy, the nonpersistence rates ranged from 5.9% to 22.6% in years 1-5, and the rate of low compliance ranged from 2.1% to 11.2% [19]. The low compliance with endocrine therapy may be partially explained by inadequate information and social support [19][20][21][22][23]. Therefore, demonstrating the similar survival rate of different surgeries and the efficacy of adherence to endocrine therapy may help physicians and women with breast cancer make better clinical decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies used self-report adherence measures. The most frequently used validated self-report measures were the Medication Adherence Rating Scale (MARS) [ 84 ], [ 4 , 31 , 49 , 78 ], the 8-item Morisky Medication Adherence Scale (MMAS-8) [ 85 ], [ 35 , 52 , 57 ], and the 4-item Morisky Medication Adherence Scale (MMAS-4) [ 86 ] [ 64 , 72 , 73 , 80 ]. Seven studies created their own adherence measure [ 38 , 53 , 58 , 67 , 69 , 70 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may be related to the increasing rate of medication discontinuation over time, or to the younger age of the study subjects and the common practice of clinical endocrine therapy for 5 years. Studies have shown that women taking a single drug for breast cancer are more likely to stop taking their medication over a period of two to three years [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%